Estimation of lung volumes from chest radiographs using shape information. Issue 6 (December 1979) - Pierce, R J; Brown, D J; Holmes, M; Cumming, G; Denison, D M
Abstract : The cross-sectional shapes of the chest and its contained structures have been assessed in post-mortem anatomical sections and from computerised tomographic scans in living subjects. These shapes are described by simple equations that can be used to increase the accuracy of measuring lung volumes from chest radiographs. Radiographic estimates of total lung capacity, using the equations, were compared with plethysmographic and single-breath helium dilution measurements in 35 normal subjects. The postures commonly used for taking chest radiographs were found, on average, to decrease total lung capacity (TLC) and to increase residual volume by about 200 ml when compared with the sitting positions used for the other two measurements (studies made in 18 of the subjects). After correction for this effect, the radiographic estimates of TLC, which measure the displacement volume of the lung, exceeded the plethysmographic estimates of contained gas volume by a mean of 720 ml, which was taken as the volume of tissue, blood, and water in the lungs. The single-breath dilution estimates of TLC fell short of the plethysmographic values by a mean of 480 ml, taken as the volume of contained gas that was inaccessible to helium in 10 seconds. The tomographic studies suggested that the radiographic technique of measuring lung displacement volumes has an accuracy of +/- 210 ml. The method is rapid and simple to use and has intra- and inter-observer variabilities of less than 1% and less than 5% respectively.